(untitled) (Journal of Human Sciences, 2021)
Perhaps we will not add anything new if we consider that the issue of values is one of the topics of central position in human thought in general, and the Arab-Islamic thought is no exception to that, and the close relationship between values and religion imposed a character of awe on the value proposition in Arab and Islamic thought, where the research was divided In the values in the Arab thought to many trends, philosophical interpretations and jurisprudential opinions that are many in the multiplicity of trends and intellectual and sectarian interpretations in the Arab Islamic community. Although the value system has been dealt with within the framework of multiple and sometimes divergent interpretations within that plurality, this does not affect the unity of values as much as it indicates that culture and knowledge are among the elements that govern the thinking and jurisprudence of value together. We believe that the difference in these trends and interpretations is due to their clarity and confusion among others, as well as the confusion caused by the lack of distinction between the absolute and the relative, or rather, between value and standard.